Antibacterial poly(4‐vinyl phenylboronic acid)‐co‐[2‐(dimethylamino)ethyl methacrylate] copolymers and their application in water‐based paints. Issue 22 (14th February 2018) - Cicek, Hüseyin; Kocak, Gökhan; Ceylan, Özgür; Kutluca, Emir Ahmet; Dikmen, Zeynep; Bütün, Vural
ABSTRACT: Herein, we report the synthesis of poly(4‐vinylphenylboronic acid) (PVPBA) and poly[2‐(dimethylamino)ethyl methacrylate] (PDMAEMA) homopolymers, copolymers, and their methyl, pentyl, and octyl quaternized forms as dopant in water‐based permanent antibacterial paints. Both quaternized and nonquaternized forms of P(VPBA ‐co‐ DMAEMA) copolymers have reflected higher MIC values relative to PDMAEMA homopolymers. High molecular weight copolymers were more active against Escherichia coli ATCC 25922, contrarily, lower molecular weight copolymers showed higher antibacterial activity against Staphylococcus aureus ATCC 25923. The paint films prepared with quaternized PDMAEMA homopolymers with a weight of 10% showed better antibacterial activity in water and airborne tests than the copolymers. However, it has been shown that the inadequate anti‐biofilm properties of homopolymer‐containing paint films are overcome with the VPBA content of the copolymer structure and the most effective antibacterial and anti‐biofilm properties have been obtained with paint films containing P(VPBA ‐co‐ 5QDMAEMA) copolymers. These paint films, which can maintain antibacterial and anti‐biofilm properties for at least 1 year, have the potential to be an alternative to Ag/Cl based solid surfaces which require the active substance to be regenerated. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46245. Abstract :